If 5x+6=10, what is the value of 10x+3?

A) 4
B) 9
C) 11
D) 20

Answers

Answer 1
Answer:

Answer: 11

Step by step explanation:

Step 1 : solve the first equation to find the value of x

5x + 6 = 10

5x = 10 – 6

5x = 4

X = 4/5

Step 2 : Substitute the value of x in the second equation

10x + 3 = ?

10 ( 4/5) + 3  

= 40 / 5 + 3

= 40 + 15 /5

= 55 / 5

= 11

Answer 2
Answer: 5x+6=10
5x=10-6
5x=4
x=4/5

If we substitute the value of x into the second equation

10x+3
10* 4/5+3
8+3=11
Therefore, your solution is 11

Related Questions

Solve the equation. -2(4x+4) -4=12 Group of answer choices -3 -0.6 -192 3
This is about slope
4m+9+m+3=2m-m+9+m+9 what is the value of m
3.25- 13 tenths A:10.25 B:3.12 C:2.95
PLEASE HELP ILL MARK Y BRANLIEST!!!

what are the solutions of the equations x^2+14x=-130? (1point) a.2,-16 b.10,-13 c.-2,16 d.no solution

Answers

x^2+14x=-130\nx^2+14x+49=-81\n(x+7)^2=-81

no solutions in \mathbb{R}

in \mathbb{C}
x+7=-√(-81) \vee x+7=√(-81)\nx=-7-√(-81) \vee x=-7+√(-81)\nx=-7-9i \vee x=-7+9i\n

Please help im desperate if f(x) = 5 + 3x find the value of the dependent variable if the if he independent variable is -4 and if you know hoew to do this pls answer my other question

Answers

Answer:

[see below]

Step-by-step explanation:

The dependent variable is considered 'y' or 'f(x)'.

The independent variable is considered 'x'.

f(x)=5+3x\n\nf(-4)=5+3(-4)\n\nf(-4)=5-12\n\n\boxed{f(-4)=-7}

Hope this helps.

Answer: the dependent variable is -7

Step-by-step explanation:

this is really simple all we have to do is plug -4 instead of x

so the equation is going to be f(-4)=5+3(-4)

now we just solve like normal so that would be...

f(-4)= 5+ -12 (3*-4 is -12)

f(-4)= -7

i hope it helps

Which is another way to check the sum of 52+23+10+78

Answers

well first off those numbers add up to 163.

A way to check this is to add 52 with 23 which is 75 then add 78 by 10 which is 88 now add 75 with 88 which is 163

Simplify 20 + (2 + r).

Answers

Answer:

The simplified form of given expression is 22+r.

Step-by-step explanation:

The given expression is

20+(2+r)

We need to find the simplified form of the given expression.

The  given expression can be written as

20+2+r

In this expression r is variable and 20, 2 are constant terms.

Now, combine constant terms.

(20+2)+r

On further simplification we get

(22)+r

22+r

Therefore, the simplified form of given expression is 22+r.

First remove the parentheses because addition is commutative. 
20+2+r
Add 20 and 2 together
r+22
Hope this helps. 

Please help Match the picture to the reason that would prove the triangles congruent.

Options:
NONE
ASA
SSS
SAS
AAS
HL

Answers

Answer is AAS hope this helps

Let f(x) = 9x − 2 and g(x) = −x + 3. Find f(g(x)).

Answers

f(x) = 9x - 2
g(x) = -x + 3

f(g(x)) = 9(-x + 3) - 2
f(g(x)) = 9(-x) + 9(3) - 2
f(g(x)) = -9x + 27 - 2
f(g(x)) = -9x + 25
f(g(x))=9(-x+3)-2
So: f(g(x)=-9x+27-2=-9x+25